Room-Temperature, Transition-Metal-Free Arylation of Alcohols with Aryl Bromides - Zhu, Da-Liang; Li, Jie; Wu, Qi; Wang, Yanqing; Young, David J.; Li, Hong-Xi (Synthesis, 2022)
Sodium tert-butoxide promotes the efficient etherification of alcohols with aryl bromides at room temperature. This simple procedure has a broad substrate scope, providing a practical pathway to aryl alkyl ethers in good yields without the addition of any transition metal species.
Keywords: alcohols; aryl bromides; transition-metal-free; aryl alkyl ethers; sodium tert-butoxide